2024
DOI: 10.1001/jamapsychiatry.2023.4127
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Liability to Posttraumatic Stress Disorder Symptoms and Its Association With Cardiometabolic and Respiratory Outcomes

Gita A. Pathak,
Kritika Singh,
Karmel W. Choi
et al.

Abstract: ImportancePosttraumatic stress disorder (PTSD) has been reported to be a risk factor for several physical and somatic symptoms. However, the genetics of PTSD and its potential association with medical outcomes remain unclear.ObjectiveTo examine disease categories and laboratory tests from electronic health records (EHRs) that are associated with PTSD polygenic scores.Design, Setting, and ParticipantsThis genetic association study was conducted from July 15, 2021, to January 24, 2023, using EHR data from partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Few studies have examined the performance of anxiety-related PGS. One study in which a PGSPTSD was tested in four EHR-based biobanks [60] showed significant associations with a PTSD diagnosis, a SUD diagnosis, and tobacco dependence, as well as numerous associations with medical conditions, including circulatory and respiratory diseases. In contrast to our findings, that study showed associations with various anxiety disorders and depression, which may have been due to the large size of the included biobanks and the higher number of cases for anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the performance of anxiety-related PGS. One study in which a PGSPTSD was tested in four EHR-based biobanks [60] showed significant associations with a PTSD diagnosis, a SUD diagnosis, and tobacco dependence, as well as numerous associations with medical conditions, including circulatory and respiratory diseases. In contrast to our findings, that study showed associations with various anxiety disorders and depression, which may have been due to the large size of the included biobanks and the higher number of cases for anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%